Caenorhabditis elegans as a model for obesity research - Yiren Yue; Sida Li; Peiyi Shen; Yeonhwa Park (Current Research in Food Science, 2021)
Caenorhabditis elegans, a free-living nematode, is an animal model that has been extensively employed in a variety of research fields, including in the study of obesity. Its favorable features include its compact size, short life cycle, large brood size, easy handling, low cost, availability of complete genetic information, 65% conserved human diseases-associated genes, relatively easy genetic manipulation, and research using Caenorhabditis elegans does not require approvals by the Institutional Animal Care and Use Committee. These advantages make Caenorhabditis elegans a great in vivo model for life science research including obesity research. In this review, we provide graphic overviews of Caenorhabditis elegans’ basic anatomy, growth conditions, routes of compound delivery, and fat metabolism, both synthesis and degradation pathways, including major signaling pathways involved. Our aim is to provide an overview for researchers interested in applying C. elegans as an in vivo model for the screening and identification of anti-obesity bioactive compounds prior to testing in vertebrate animal models.